Peran kepemimpinan transformasional, komitmen organisasi dan budaya organisasi terhadap kinerja pegawai - Lailatul Hikmah; Alivia Mujaya; Boge Triatmanto (University of Merdeka Malang, 2023)
This research aims to analyze the role of transformational leadership, organizational commitment, organizational culture on employee performance at the Malang City P3AP2KB Social Service. The data collection technique used a questionnaire with a sample of 60 respondents who worked at the Malang City P3AP2KB Social Service. The analytical tool used is the multiple linear analysis test. The results of the description of a picture in this study state that the independent variable transformational leadership has the highest score (mean) across all indicators of the other independent variables with more agree answers. In this way, the transformational leadership of the Malang City P3AP2KB Social Service has been very good and achieved. The results of the analysis in this study show that transformational leadership, organizational commitment, and organizational culture have a significant effect on the performance of Malang City P3AP2KB Social Service employees. Organizational commitment has a dominant influence on employee performance at the Malang City P3AP2KB Social Service.